2018
DOI: 10.1155/2018/4179312
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Axial Vibration on Sliding Frictional Force between Shale and 45 Steel

Abstract: Activating drill string vibration is an effective means to mitigate the excessive drag encountered during drilling complexstructure wells. However, the Coulomb model cannot describe the sliding friction behavior between drill string and borehole rock with imposed axial vibrations. To solve this problem, a specially designed experimental setup was utilized to investigate the characteristics of axial vibrating-sliding coupling friction. The results indicate that when vibration velocity is greater than sliding ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As in the case of concrete, it is also difficult to determine unambiguously the value of the friction coefficient in the contact zone between the undercutting head and the rock, because in many cases, before the actual detachment occurs, the rock is crushed, causing a significant change in the friction and contact conditions. The authors of a number of studies on anchoring give a fairly wide range of values for the coefficient of friction of the medium against the steel or carbide from which the mining tool is made [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of concrete, it is also difficult to determine unambiguously the value of the friction coefficient in the contact zone between the undercutting head and the rock, because in many cases, before the actual detachment occurs, the rock is crushed, causing a significant change in the friction and contact conditions. The authors of a number of studies on anchoring give a fairly wide range of values for the coefficient of friction of the medium against the steel or carbide from which the mining tool is made [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of antifriction technology, many investigations have been made to solve this problem. [1][2][3][4][5][6] Various tools such as agitator have been developed and designed to resolve contradictions and improve the extended limits of horizontal wells. [7][8][9] Engineering applications have shown that a small number of anti-frictional tools, such as agitator, had a certain effect on drilling engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the process of learning the analytical formula of weight can be well defined. Therefore, the back propagation network realize the nonlinear mapping of arbitrary inputs to outputs as per the real-world working conditions [ [10] , [11] , [12] , [13] , [14] ].…”
mentioning
confidence: 99%